Time in Service and Resilience in Active Military Personnel during the COVID-19 Pandemic: A Cross-Sectional Study in Northern Peru - Valladares-Garrido, Mario J. (2022)
“Greater occupational exposure may have a positive effect on the development of resilience. We aimed to determine the association between working time and resilience in Peruvian military personnel during the COVID-19 pandemic. A secondary data analysis was performed including 586 records of military personnel who supported the health emergency during the second epidemic wave in Lambayeque, Peru. Resilience was measured with the short form of the Connor-Davidson Resilience Scale (CD-RISC). Working time and other relevant covariates were collected by self-report. Generalized linear models were used. The mean resilience score was 22.18 and 43.2% scored high for resilience. Participants reported that they are strong individuals when facing difficulties (42.3%), are able to handle unpleasant feelings (40.3%), and achieve their goals despite obstacles (40.4%). Working more than 18 months was associated with a 35% higher prevalence of high resilience (PR: 1.35; 95% CI: 1.05–1.75). In conclusion, a notable number of military personnel experienced high levels of resilience during the pandemic. Working time may have played an important role in the development of this ability. Our findings could help guide the deployment and organization of the military in health emergency support missions.“